Persistence in a pharmacist-led, same-day PrEP program in Mississippi: a mixed-methods study - Christine M. Khosropour; Taylor Riley; Elise Healy; Kandis V. Backus; Courtney E. Gomillia; Leandro Mena; Khadijra R. Lockwood; Felicia M. Gordon; Arianna R. Means; Lori M. Ward (BMC, 2023)
Abstract Introduction Mississippi has one of the highest rates of HIV in the United States but low PrEP uptake. Understanding patterns of PrEP use can improve PrEP initiation and persistence. Methods This is a mixed-method evaluation of a PrEP program in Jackson, Mississippi. Between November 2018-December 2019, clients at high risk for HIV attending a non-clinical testing site were referred to a pharmacist for same-day PrEP initiation. The pharmacist provided a 90-day PrEP prescription and scheduled a follow-up clinical appointment within three months. We linked client records from this visit to electronic health records from the two largest PrEP clinics in Jackson to determine linkage into ongoing clinical care. We identified four distinct PrEP use patterns, which we used for qualitative interview sampling: 1) filled a prescription and linked into care within three months; 2) filled a prescription and linked into care after three months; 3) filled a prescription and never linked into care; and 4) never filled a prescription. In 2021, we purposively sampled patients in these four groups for individual interviews to ascertain barriers and facilitators to PrEP initiation and persistence, using guides informed by the Theory of Planned Behavior. Results There were 121 clients evaluated for PrEP; all were given a prescription. One-third were less than 25 years old, 77% were Black, and 59% were cisgender men who have sex with men. One-quarter (26%) never filled their PrEP prescription, 44% picked up the prescription but never linked into clinical care, 12% linked into care at some point after three months (resulting in a gap in PrEP coverage), and 18% linked into care within 3 months. We interviewed 26 of 121 clients. Qualitative data revealed that cost, stigmas related to sexuality and HIV, misinformation about PrEP, and perceived side effects were barriers to uptake and persistence. Individuals' desire to stay healthy and the support of PrEP clinic staff were facilitators. Conclusions The majority of individuals given a same-day PrEP prescription either never started PrEP or stopped PrEP within the first three months. Addressing noted barriers of stigma and misinformation and reducing structural barriers may increase PrEP initiation and persistence.